Civil Society Engagement Under Local Decentralization: An Assessment of CSO Participation in Tangub City Governance - Angelie Anggot; Christine Tenorio; Hazel Jovita-Olvez,; Eucil Hussein (Internasional Journal of Politics and Public Policy, 2026)
This study analyzes the participation, purposes, and challenges of civil society organizations (CSOs) in local decision-making in Tangub City. Using a mixed-method approach, five representatives were purposively selected from fourteen accredited CSOs based on active involvement and organizational performance. Purposeful sampling enables the selection of information-rich cases and aligns with evidence that data saturation is often achieved with a limited number of interviews. The findings show that CSOs consistently engage in program implementation and consultations, frequently participate in development planning, and occasionally contribute to monitoring and evaluation. Their main objectives are to promote public participation and provide essential community services. However, CSOs face constraints including limited financial capacity, weak legislative support, low institutional awareness, and the absence of a coordinating focal person. Strengthening capacity-building programs, improving documentation practices, and enhancing collaboration with stakeholders are recommended to improve the effectiveness of CSO participation in local governance.